Interview with Brian Cheung, Yahoo! Finance - Malpass, David (World Bank, Washington, DC, 2021)
World Bank Group President David Malpass spoke about the need for more transparency in all of the contracts that are between the COVAX manufacturers and the intermediaries, so the World Bank Group and others can find ways to provide additionality. The need now is to have more supply and more shipments going to the people that are most in need. The direction that the world needs to head is toward a greener, more resilient, more inclusive recovery. The World Bank is by far the biggest financier globally of climate-related efforts by countries. It is very important for the people to know what contracts have been entered into by their governments. The World Bank is working with the countries directly on what are called the NDCs, the nationally determined contributions, which is the relationship that countries have with the Paris Agreement. He was pleased with the things that the Biden Administration is saying about the need for real transformation in the greenhouse gas area.